Zambia : Request for an Arrangement Under the Extended Credit Facility-Press Release; Staff Report; Staff Supplement; Staff Statement; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report ;, 2022)
Zambia is dealing with large fiscal and external imbalances resulting from years of economic mismanagement, especially an overly ambitious public investment drive that did not yield any significant boost to growth or revenues. A drought in 2019 and the COVID-19 pandemic exacerbated the acute economic and social challenges facing the country, with poverty, inequality, and malnutrition rates amongst the highest in the world. As a result, Zambia is in debt distress, defaulting on its Eurobonds in November 2020 while also accumulating arrears to other creditors. The war in Ukraine has increased prices of fuel and fertilizer, amplifying pressures further.